La redécouverte de l’Autre par écrans interposés - Ioanna Vovou; Angeliki Koukoutsaki-Monnier (Communication)
The aim of this article is to examine the evolution of the mise-en-scène of Greco-Turkish relations as they have been constructed in Greek television series over the last forty years (1967-2007). Firstly, a diachronic sheds light on the global evolutions which operate in television fiction related to this subject. Following this, some time is spent analysing the first Turkish series recently presented in Greece. The diagetic discourse proposed by Yabanci Damat (The Foreign Son-in-Law), known in Greece as, Ta Synora ths agaphs (The Borders of Love), is studied in terms of the symbiosis between different cultural identities suggesting, beyond representations of the Other, that of oneself through the eyes of the Other.